Hip fractures in Chinese TikTok (Douyin) short videos: an analysis of information quality, content and user comment attitudes - Li, Zhuoxin; Lin, Yashi; Zhang, Kairou; Li, Ran; Ju, Mei; Chen, Yanhua; Fu, Jing; Huang, Ruiyu; Zhu, Ling; Sun, Junjun; Guo, Yanxia; Gao, Min; et al. (Frontiers in Public Health, 2025)
BackgroundHip fracture presents a major healthcare challenge globally. While numerous Douyin videos address hip fracture, their information quality and factors affecting user comment attitudes remain uncertain.ObjectiveThis study aims to analyze the content, information quality, and user comment attitudes of videos depicting hip fractures on Chinese TikTok (Douyin).MethodsThe search term “hip fracture” was used on Douyin, which resulted in 170 samples being included. Video information quality was assessed using the GQS and PEMAT scales. Video content was analyzed using DivoMiner. User comments were extracted using Gooseeker, and user comment attitudes were interpreted as positive, neutral, or negative using the Weiciyun website. Data analysis was performed using IBM SPSS version 29.0, including non-parametric tests for continuous variables and chi-square tests for categorical variables. The identified factors were then included in a multivariate logistic regression analysis to examine their impact on user comment attitudes.ResultsHealth professionals were the primary source of videos (136/138, 98.6%). The overall information quality of the videos was moderate (median 3, IQR 2.00–4.00). Douyin videos were relatively high in understandability (median 72.70%, IQR 63.60–81.80%) but low in actionability (median 33.33%, IQR 0–66.67%). Most videos focused on treatment (139/170, 81.8%). Regarding user comment attitudes, the majority of videos were received with positive comments (113/170, 66.5%), followed by negative comments (39/170, 22.9%) and neutral comments (18/170, 10.6%). The multivariate logistic regression analysis revealed three factors influencing positive attitudes: the GQS score (OR 13.824, 95% CI 6.033–31.676), understandability (OR 2.281, 95% CI 1.542–5.163) and not mentioning risk factors in videos (OR 0.291, 95%CI 0.091–0.931).ConclusionThe majority of hip fracture videos on Douyin were created by health professionals and had intermediate information quality, with user comment attitudes remaining positive. However, these videos often lacked actionability and had insufficient mention of prevention and rehabilitation content. Videos with higher information quality that addressed hip fracture risk factors received more positive user comments. This study suggests that publishers of hip fracture-related videos should improve actionability while simultaneously paying attention to both prevention and rehabilitation content to enhance the educational value of these videos.